Effect of acute exposure of lead acetates on the morphology of liver and kidney of mice (Mus musculus) and the role of vitamin C as a repairing agent - Ishraq J. H; Wissam S.H. Al-Uboody; M.A. Al-Diwan (Basrah Journal of Veterinary Research)
The objective of this study is to elicit the destructive effect of lead on the tissues of liver and kidney of mice and if vitamin C is capable of repairing the damage caused by lead. In this study, 40 male mice were used and divided into three groups as: Control group which consists of 16 mice; 8 of them were injected intraperitoneally with (0.9 % N.S.) for 15 days daily then they were sacrificed and the remainder 8 mice were injected intraperitoneally with (0.9 % N.S.) for additional 15 days daily then they were sacrificed, First treated group (T1 group) which consists of 8 mice only; they were injected intraperitoneally with (80 mg/kg) lead acetates then with (400 mg/kg) vitamin C after one hour of lead acetates injection for 15 days daily then they were sacrificed, Second treated group(T2 group) which consists of 16 mice; they were injected intraperitoneally with (80 mg/kg) lead acetates for 15 days daily then 8 of them were sacrificed and called as (T2a) and the remainder 8 mice were injected with (400 mg/kg) vitamin C for additional 15 days daily and called as (T2b). Histologically, the kidneys of the lead acetates treated group indicated undefined epithelial cell lining and also the presence of giant-like cells. When vitamin C offered, it decreased the damage that caused by lead where the kidneys indicated the presence of cuboidal epithelial cells with disrupted epithelial cell lining, and increased intracellular space in the lumen. The livers of the lead acetates treated group indicated the presence of abnormal hepatocytes with distorted shape and undefined epithelial cell lining enlarged nucleus with vacuolations. The incidence of changes and severity were less in the vitamin C treated group. The effect of vitamin C was similar if it is offered after one hour of lead injection or for additional 15 days after lead injection. Hence acute exposure to lead causes morphological changes in the liver and kidney of mice. Hence acute exposure of lead may be toxic and is associated with various pathological conditions such as hepatic and renal dysfunction and cancers.